Development of Entrepreneurial Spirit and Women Empowerment at Pesantren Griya Khadijah Surabaya through Diversification Training on Fishery Products as Food Commodities with High Nutritional Value - Putri Desi Wulan Sari; Luthfiana Aprilianita Sari; Rahayu Kusdarwati (Kontribusia : Research Dissemination for Community Development, 2021)
The development of an entrepreneurial spirit can be started even with minimal capital. Fishery products with high nutritional value are one of the opportunities that can be developed by community groups as independent businesses in the context of increasing the economy. Santriwati at the Griya Khadijah Islamic Boarding School Surabaya is a national asset that has great potential, role, and opportunity in influencing the social and economic life of the surrounding community. This community service activity aims to improve the competence of female students at the Griya Khadijah Islamic Boarding School, as a role model for hafidzah-preneur education, to be able to develop an entrepreneurial spirit and reflect women's empowerement with good character.